The association of NPHS1 and ACNT4 gene polymorphisms with pre-eclampsia. (November 2021) - Khaliq, Olive P; Konoshita, Tadashi; Moodley, Jagidesa; Naicker, Thajasvarie
Abstract: Objective: The main objective of this study is to investigate the association of the NPHS1 gene polymorphisms (rs437168) and ACTN4 (rs3745895) in the pathogenesis of PE in women of African Ancestry. Materials and methods: 637 blood samples, normotensive pregnant (n = 280) and pre-eclampsia (n = 357) were included. The PE group was sub-divided into early onset pre-eclampsia (n = 187) and late onset pre-eclampsia (n = 170). rs74315346, rs869025495, rs121908415, rs3745895, and rs437168 were genotyped from isolated DNA using real time PCR. Results: The C allele of rs437168 ( NPHS1 ) was significantly higher in PE compared to controls. [C vs T; p  = 0.0323* ] and [CC vs CT/TT; p  = 0.0464* ]. A comparison between the subtypes of PE and controls showed that the C allele was significantly higher in EOPE compared to controls [ p  = 0.0027 ** ], [CC vs CT/TT; p  = 0.0111* ], [CC/CT vs TT p  = 0.0198* ] and LOPE. [ p  = 0.0259* ]. The other SNPs genotyped showed no signification associations with PE. Conclusion: This study found that the C allele of rs437168 is significantly associated with the pathogenesis of early onset PE and may be accountable for renal injury, which is a risk factor for the development of EOPE in women of African Ancestry.